2002
DOI: 10.5194/npg-9-149-2002
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and singularity characteristics of solar wind and magnetospheric fluctuations

Abstract: Preliminary results are presented which suggest that scaling and singularity characteristics of solar wind and ground based magnetic fluctuations appear to be a significant component in the solar wind -magnetosphere interaction processes. Of key importance is the intermittence of the "magnetic turbulence" as seen in ground based and solar wind magnetic data. The methods used in this paper (estimation of flatness and multifractal spectra) are commonly used in the studies of fluid or MHD turbulence. The results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…As a consequence, the associated probability density functions (PDF's) are non-Gaussian. It has been shown by Vörös et al (2002) and Dorotovic and Vörös (2004) that intermittent fluctuations in the solar wind affect the geomagnetic response. By comparing solar wind data obtained from the ACE spacecraft with plasma sheet data from the Geotail mission, Dorotovic and Vörös (2004) suggested that the non-Gaussian characteristics of the PDF's of solar wind data can be interconnected to the occurrence of intermittency in the magnetic fluctuations in the plasma sheet.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the associated probability density functions (PDF's) are non-Gaussian. It has been shown by Vörös et al (2002) and Dorotovic and Vörös (2004) that intermittent fluctuations in the solar wind affect the geomagnetic response. By comparing solar wind data obtained from the ACE spacecraft with plasma sheet data from the Geotail mission, Dorotovic and Vörös (2004) suggested that the non-Gaussian characteristics of the PDF's of solar wind data can be interconnected to the occurrence of intermittency in the magnetic fluctuations in the plasma sheet.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates quantitative "comparative" studies of scaling in time series (e.g. Takalo and Timonen, 1998;Freeman et al, 2000;Uritsky et al, 2001;Vörös et al, 2002;Hnat et al, 2003a). Such studies can to some extent fruitfully consider the low order moments, whereas a particular difficulty for comparison of observations with models of turbulence is that the intermittency parameter in turbulence τ (2) is determined by the 6th order structure function .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on scaling and singularity characteristics of geomagnetic fluctuations into the MHD flow system, considering solar wind and ionosphere phenomena, suggest that the nearEarth magnetosphere is a non-homogenous interconnecting multi-scale environment where spatio-temporal variability is intermittent. In this inhomogeneous scenario, multifractal turbulence can coexist with coherent global processes and self-organized criticality involving the singular behavior of the energy distribution in physical space resulting in strong gradients (Vörös et al, 2002). Such strong variations constitute the intermittency pattern in the time-series, usually a measurement of the energy related to the physical quantities of the system, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…A usual hypothesis is that the intermittency behavior is associated with the multifractal turbulence model (Muzy et al, 1991). This fact suggests that the fluctuations can be described by means of a multifractal scaling law which is associated with intermittency, then admitting that nonlinear and coherent processes can coexist (Vörös et al, 2002;Weygand et al, 2005;Wanliss et al, 2005). Thus, the present study deals with the multifractal analyses of low-latitude geomagnetic H -field records which is fully intermittent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation